Data Management Plan for ESRC project "Young children’s embodied engagement with storyworlds: Attuning to movement and affect while playing with stories as an inclusive reading practice." - Samantha Hulston (22269946) (2025)
My research contends that young children make meanings with their bodies. Yet, in classrooms there is an emphasis on children talking about stories, overlooking the body’s role in meaning-making and disadvantaging those with diverse communicative competencies. To redress this imbalance, my research explores young children’s embodied engagement with the storyworlds depicted in picturebooks. Bridging research with practice, I positioned myself as a class adult, designing a novel play-based activity to foreground young children’s embodied engagement with storyworlds. Video observations of play were innovatively analysed by attending to the interplay between movement and affect, surfacing the unseen elements of embodied engagement. This cutting-edge approach illuminated how young children used fluctuations in movements and shifts in proximity to extend and deepen their engagement with storyworlds. Significantly, this fluidity arose as children interacted with objects and individuals. Deviating from dominant understandings in literacy research, my findings advanced an original conceptualisation of young children’s embodied engagement as relational and distributed. Class adults occupy salient contingent and generative roles within this conceptualisation, with their movements reacting to but also influencing children’s embodied engagement. These findings matter to teachers, highlighting how embodied approaches can support young children’s reading engagement as a route to reading enjoyment. I argue for changes to education practice and policy so that young children’s embodied engagement is valued and embedded as part of reading.